Comparison of a standardized negative pressure wound therapy protocol after midline celiotomy to primary skin closure and traditional open wound vacuum-assisted closure management. Issue 1 (2nd January 2018) - Regner, Justin L.; Forestiere, Matthew J.; Munoz-Maldonado, Yolanda; Frazee, Richard; Isbell, Travis S.; Isbell, Claire L.; Smith, Randall W.; Abernathy, Stephen W.
Abstract: A negative pressure wound therapy (NPWT) protocol using Hydrofera Blue® bacteriostatic foam wicks and silver-impregnated foam overlay to close midline skin incisions after emergency celiotomy was compared to primary skin closure only and traditional open wound vacuum-assisted closure management as part of a quality improvement initiative. This single-institution retrospective cohort study assessed all consecutive emergency celiotomies from July 2013 to June 2014 excluding clean wounds. Included variables were demographics, wound classification, NPWT days, and surgical site occurrences (SSOs). Primary outcome was days of NPWT. Secondary outcomes included SSOs (surgical site infections, fascial dehiscence, return to operating room). Analysis used exact chi-square between categorical variables, Kruskal-Wallis for analysis of variance for ordinal and categorical variables, and Wilcoxon rank sum for total days of NPWT. One hundred fifty-eight patients underwent emergency celiotomy with primary skin closure ( n = 51), open NPWT ( n = 63), or the NPWT protocol ( n = 44). There was no difference in American Society of Anesthesiologists Physical Status score, body mass index, wound classification, or SSO between the three groups. Total NPWT days were reduced in protocol versus open NPWT (median 3 vs 20.5 days, range 3–51 vs 3–405 days, P = 0.001). Primary skin closure and NPWT protocol had fewer patients discharged with NPWT than open NWPT (0% and 14% vs 63.5%, P < 0.0001, odds ratio = 10.7, 95% confidence interval 3.7–35.1). Primary skin closure and NPWT protocol decrease NPWT usage days and maintain low SSOs in emergency midline celiotomy incisions.